The state of preparedness of prospective physical education and sports teachers - Yilmaz, Metin; Karakaya, Yunus E.; Savucu, Yuksel (Iermakov S S, 2020)
Purpose: This study was conducted to determine the state of readiness of prospective physical education and sports teachers, who were studying in sports education institutions in Turkey. Material: The sample of the study consisted of 552 prospective physical education and sports teachers, who were chosen by the random sampling method. To collect the data from the sample group, the Preparedness for Teach Scale, which consisted of 20 items and 4 subscales. The collected data were analysed for normality by using SPSS 22.0 package software. Because the data demonstrated a normal distribution, the Independent Samples t-testsand One-way ANOVA tests were conducted. To determine the level of relationship between dependent variables, Pearson Correlation Analysis was conducted. Results: In the gender variable of the sample group, statistically significant differences were observed in the subscales of Designing the instructional process and Understanding the learner. In the grade variable, significant differences were determined in the subscales of Forming and effective learning atmosphere, Designing the instructional process and Techno-pedagogical competence. In the variable of the department of education, significant differences were determined in all the subscales. Because of the correlation analysis, it was observed that there were positive and strong correlations between the subscales of Forming an effective learning atmosphere and Designing the instructional process (r= 0.807; p<0.05). Conclusions: For teachers to become more confident in themselves and develop their competencies more positively, it will be beneficial to enlarge professional standards and teaching framework.Within this scope, considering the results obtained from the study, it will be beneficial to create positive classroom environments and to ensure that prospective teachers benefit from teachers' experiences to improve their preparedness to professional life. The study indicated that the competencies of prospective teachers towards the profession of teaching were generally positive. It was observed that several factors affected prospective physical education and sports teachers in their preparedness for teaching. Thus, it is important to ensure that prospective physical education and sports teachers gain acquisitions for their general competencies in the profession of teaching before they complete their undergraduate education.
Keywords: higher education; sports education; prospective teachers; preparedness; physical education